Foley Catheter with Peri-Urethral Antimicrobial Irrigation for the Prevention of Catheter Associated Urinary Tract Infections – Assessment in an In Vitro Model. (4th October 2017) - Rosenblatt, Joel; Reitzel, Ruth; Vargas-Cruz, Nylev; Chaftari, Anne-Marie; Hachem, Ray Y; Raad, Issam
Abstract: Background: Catheter associated urinary tract infections (CAUTIs) are a significant medical issue with substantial morbidities and costs. CAUTIs are primarily caused by colonization of the external surface of Foley catheters which serve as conduits for colonizing microbes to access the bladder. In order to prevent these CAUTIs, we developed a double-cuff Foley catheter with a novel irrigation cuff for daily irrigation of the periurethral space with a biocompatible antimicrobial disinfecting solution. This study assessed the efficacy of this system for reducing external-surface microbial colonization of catheters in an in vitro model. Methods: The novel double cuff Foley and disinfectant solutions were evaluated in an established in vitro CAUTI model (Gaonkar, et al 2003) where a Foley catheter indwelled in a simulated urethra. 5.5 × 10 5 CFU of common uropathogens (MRSA, E. coli, C. albicans ) were allowed to attach to the external catheter surface at meatal end of the catheter for 2 hours at 37°C. Subsequently, 3 mL of disinfectant solutions were instilled through the irrigation cuff and covered the periurethral catheter surfaces. Catheters were then incubated an additional 24–48 hours at 37°C, removed, cut into segments, and adherent organisms were quantified by sonication. Disinfectant solutions evaluated included various combinations of 1% polygalacturonic acid (PG), 0.4% caprylic acid (CAP) and (dilute) 0.3% H2 O2 . Results: For all organisms tested only the triple combination periurtehral flush (PG+CAP+H2 O2 ) completely prevented biofilm colonization of catheters indicating antimicrobial synergy of the component agents. Control catheters grew >10 4 CFU/segment. Single agent or double agents combinations were only partially effective in preventing colonization by all three pathogens. Conclusion: The PG + CAP + H2 O2 periurethral disinfectant flush instilled through an irrigation cuff in a novel double-cuff Foley catheter was able to completely prevent microbial colonization of the external catheter surface by MRSA, E. coli and C. albicans in an in vitro CAUTI model. In vivo studies are needed to further evaluate this technology for prevention of CAUTI. Disclosures: J. Rosenblatt, Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a and Shareholder, Licensing agreement or royalty; UT MD Anderson Cancer Center: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a s and Scientific Advisor, Licensing agreement or royalty; I. Raad, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant; Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Raad is a s and Shareholder, Licensing agreement or royalty